Recognition of Local Communities: A Polycentric Model of Policy Management of Mangrove Ecosystems - Peten, Yasinta Y. Palan; Sius, Karolus T.; Hadi, Norbertus J.; Dau, Agnes; Ratumakin, Paulus Adrianus K.L (Yayasan Ilomata, 2024)
Mangrove forests are important resources that provide various ecosystem services ecologically, economically, socially, and culturally. However, the utilisation of mangrove ecosystems often faces management conflicts. Conflicts can occur between residents in the mangrove area or between agencies and levels of authority. The diversity of governance from various decentralised, connected and functionally different layers implies a complex system. The polycentric model is one approach to addressing the system's complexity. This study uses a qualitative approach with data collection techniques using interviews and observations. The aim is to examine the recognition of residents and the government for local community initiatives. This study found several essential things. First, the context of authority over the mangrove location by supra-village agencies, but in several decades, it has become a conservation and management area for residents. Second, recipients of ecosystem services and their utilisation involve residents from outside the administrative boundaries of the village. Third, cross-sector and level agreements for recognising mangrove ecosystem management initiatives based on local community wisdom. The model of recognition and autonomy given to local communities by higher authorities is the basis for sustainable polycentric governance of mangrove ecosystems. De facto autonomy includes four aspects, including: autonomy in decision-making, formal recognition, cross-actor collaboration, and control over access to resources.